A holistic approach to mobile robot navigation using omnidirectional vision - Winters, Niall (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2002)
This dissertation presents a novel methodology for vision-based robot navigation. One of the key observations is that navigation systems should be designed through a holistic approach, encompassing aspects of sensor design, choice of adequate spatial representations with associated global localisation and local control schemes.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin